2013 Bahamas International Symposium Conference Booklet - Gangelhoff, Christine (International Journal of Bahamian Studies, 2013)
Nassau Music Society & the College of the Bahamas present the 2013 Bahamas International Symposium on Composers of African and Afro-Caribbean Descent.